Collective identities, nationalisms, and protest in modern Sri Lanka. - Roberts, Michael (Colombo Marga Institute, 1979)
Includes contributed essays on various topics relating to political, nationalism, religion, ethnic relations, etc., in Sri Lanka.
Includes bibliographical references and index.
Keywords: Nationalism; Sri Lanka -- Politics and government; Sri Lanka -- Ethnic relations